Rural Nursing In Singapore - Desley Hegney (Rural Nurse Organization; Binghamton University, 2012)
Greetings to all of you from tropical Singapore. Many of you will not have realised that I moved from Australia to Singapore in March this year. In many ways I could no longer consider myself to be 'rural' living in a highly urbanised Asian city of 4.5million people. It is really every rural nurse's dream - one huge shopping centre. Really there is not much more to do here than shop and eat. Exercise is a challenge as it is hot (about 24C in the morning and gets up to 34C in the evening) and humid. But it does rain a lot (which is a refreshing change from Australia) and everything is green. No drought or water shortage, though they do not waste water either. Of course, we are only a bridge and a causeway from Malaysia or a boat ride to Indonesia. Many Singaporeans go to Indonesia and Malaysia daily to play golf, shop or visit one of the lovely resorts.